DESIGN OF LIGHTNING PROTECTION SYSTEM FOR OIL AND GAS TANKS USING 3-D MODELING ROLLING SPHERE METHOD - Ahmad Rizky, Dwisyah
The Lightning Protection System (LPS) plays an important role in protecting oil and gas tanks from the destructive effects of lightning strikes. Oil and gas tanks are vulnerable to lightning strikes due to their large surface area and flammable contents. Lightning can cause fires, explosions, structural damage and environmental hazards, so it is important to apply a strong LPS. The examination of safety systems in gas and oil tanks is frequently restricted to a two-dimensional method, which could not be effective enough to safeguard the entire tank. Consequently, the goal of this study is to conduct a three-dimensional analysis of the protective system to offer a more thorough understanding of the potential advantages and benefits of this methodology. Through the Decision matrix, the EMT and FSM design is taken as the best Lightning Protection System, which is proven through simulation that the system can reduce the number of air terminals installation by about 50%-58% than the conventional system. The author has simulated a 3-dimensional protection system that has fewer EMT and FSM installations than the 2-dimensional simulation, where the system uses 77 air terminals and can protect an area of 207,783.12m2 for the Plaju area.